From Aspirations to Occupations : The Role of Information in Educational and Labor Market Decisions in Moldova - World Bank Group (World Bank, Washington, DC, 2016)
This report sheds light on information sources and on gaps in educational and occupational choices in Moldova by presenting findings based on original data collected in 2015. To support the government in reinforcing Moldova’s career guidance and information systems for education and jobs, individual interviews and focus group discussions were conducted during the 2015 school year with secondary and tertiary students, graduates, parents, and teachers. The data address, for the first time in Moldova, issues related to how students make choices, what information they use and what they lack, and what assistance they find useful. As previously noted, one issue with career guidance in Moldova is that non‐school actors are only minimally involved in such activities. This report highlights how career guidance involves numerous actors well beyond the education system by examining the sources of information that students use and extensively reviewing international experience. The remainder of the report is organized as follows: section two describes the methodology of the study, with an overview of what factors into educational and occupational choices and the data used to assess the role of information in Moldova. Section three presents the main findings from both quantitative and qualitative data. Section four discusses the policy implications of the findings and presents examples from other countries of systematic educational information and career guidance that could be useful in designing reforms in Moldova.